Stylistic Dynamics of the Russian (Soviet) Avant-Garde in the Architecture of Novosibirsk - Bagrova, Natalya; Filonov, Sergey (project baikal, 2019)
This paper is dedicated to the problem of studying the communication potential of Russian avant-garde stylistics in architecture of Novosibirsk as a basis of actual progression from the position of discursive analysis. Continuity of elements of rational modern style, directions of avant-garde and post-constructivism style is in consideration as a genetic base. Distinguishing features of local interpretation of semantics of post-constructivism style in Novosibirsk are reviewed.